Teologi Feminis dan Dinamika Kesetaraan Gender dalam Pelayanan Gereja di Tengah Globalisasi - Yohana Fajar Rahayu; Elisa Nimbo Sumual; Yonatan Alex Arifianto (Fidei: Jurnal Teologi Sistematika dan Praktika, 2026)
Modern globalisation has brought significant changes to various aspects of life, including social dynamics and religious practices in the church, which demand new theological reflection on gender roles. Gender inequality remains a major issue, with women often experiencing limitations in their access to leadership positions and full participation in church ministry. On the other hand, traditional theology tends to maintain a patriarchal paradigm that limits perspectives on gender equality and influences pastoral practices. This study aims to analyse the contribution of feminist theology in shaping the dynamics of gender equality in church ministry amid modern globalisation. Using a qualitative research method with a literature review approach, it can be concluded that feminist theology serves as a critical framework that challenges patriarchal paradigms in theology and church practice. Through a biblical reinterpretation that is sensitive to women's experiences, feminist theology opens up a space for a more just and equal understanding of gender relations. The dynamics of gender equality in church structures and ministry require institutional and cultural transformation. AbstrakGlobalisasi modern telah membawa perubahan signifikan dalam berbagai aspek kehidupan, termasuk dinamika sosial dan praktik keagamaan di gereja, yang menuntut refleksi teologis baru terkait peran gender. Ketimpangan gender masih menjadi isu utama, di mana perempuan seringkali mengalami keterbatasan dalam akses terhadap posisi kepemimpinan dan partisipasi penuh dalam pelayanan gereja. Di sisi lain, teologi tradisional cenderung mempertahankan paradigma patriarkal yang membatasi perspektif kesetaraan gender dan mempengaruhi praktik pastoral. Penelitian ini bertujuan untuk menganalisis kontribusi teologi feminis dalam membentuk dinamika kesetaraan gender dalam pelayanan gereja di tengah globalisasi modern. Metode penelitian yang digunakan adalah kualitatif dengan pendekatan studi pustaka, dapat disimpulkan bahwa teologi feminis berfungsi sebagai kerangka kritis yang menantang paradigma patriarkal dalam teologi dan praktik gereja. Melalui reinterpretasi biblika yang sensitif terhadap pengalaman perempuan, teologi feminis membuka ruang pemahaman yang lebih adil dan setara terhadap relasi gender. Dinamika kesetaraan gender dalam struktur dan pelayanan gereja menuntut transformasi institusional dan kultural.